Perancangan Basis Data Sistem Reservasi Wisma Universitas Terbuka dengan Metode Database Life Cycle - Trihapningsari, Denisha; Putri, Mayang Anglingsari (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
The current of wisma’s Universita Terbuka reservation system still faces various obstacles, especially related to data consistency and integrity anomalies. This problem causes errors in recording and confusion in the transaction process, such as duplication of invoice numbers, which in turn can reduce reporting accuracy. This research aims to design a basis data for the Open University guesthouse reservation system using the Basis data Life Cycle (DBLC) method. This method includes several stages, starting from needs analysis, conceptual, logical, and physical basis data design. The results show a well-structured and optimized basis data design, which supports the management of reservation data, check-in, check-out, and room reservation management. The normalization process to achieve Third Normal (3NF) ensures that the data is free from redundancy and remains consistent. The physical model of the basis data is implemented using SQL queries, which are ready to be applied to a Basis data Management System (DBMS). The designed basis data is expected to improve operational efficiency, record accuracy, and maintain data integrity in the Open University guesthouse reservation system. This research is also expected to contribute to the development of literature on systematic life cycle-based basis data design.